Sociopedagogical strategy for the higher technician's nursing training in Ecuador - Rosangela Caicedo Quiroz; Mirelli del Pilar Caicedo Quiroz; Julia Esther Céspedes Acuña; Rosa Ana Jaime Ojea (Centro Provincial de Información de Ciencias Médicas, 2016)
The strategies, as a scientific result of their investigative function are usually associated to the planning process as well as the projects, fundamentally to the administrative ambition or an axiologic basis related to the institutional interests; however, these coincide when being instituted as a process that describes an organized action to achieve aims or objectives, and which operate in the context where it arises and develops.  In this work a sociopedagogical strategy for the higher technician's nursing training in the prevention of diseases is presented, starting from its link with the community.